Kesulitan Pengelolaan Pembelajaran Oline di Era Digital Selama Pandemic Covid-19: Studi Empiris di Madrasah Tsanawiyah di Bengkulu - Firdaus Muttaqin (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Difficulties in overcoming the management of online learning in the digital era are due to the level of availability of technological devices, the readiness of human resources, the level of technological literacy of teachers, students, and parents, and the readiness of educational institutions. The goal is to map and analyze the form of efforts to overcome the difficulties of online learning in the digital era during the Covid-19 pandemic. Using descriptive qualitative methods, data were collected through primary data and secondary data. Secondary data from the Tsanawiyah madrasah in Bengkulu. Primary data includes teacher profiling, motivation, type of difficulty and efforts to overcome the difficulties they experience. Secondary data consists of teacher literacy and attendance, statistics on teacher competency test results. Primary and secondary data were analyzed as an effort to overcome the difficulties of managing online learning in the digital era during the Covid-19 pandemic, taking into account their specific characteristics, situations and cultures. The study shows that differences in the socioeconomic groups of students and parents make up their chances of learning online. The gap in students' socio-economic classes has the consequence of the difficulty of managing online learning in communicating, responding, activating, collaborating and achieving student competencies and achievements. The existing structural gap is an important factor in interpreting the reality of the difficulties in managing online learning at Madrasah Tsanawiyah in Bengkulu. Keywords: Difficulties in Managing Online Learning, Digital Era, Empirical Study at Madrasah Tsanawiyah Bengkulu Abstak: Kesulitan mengatasi pengelolaan pembelajaran online di era digital, dikarenakan tingkat ketersediaan perangkat teknologi, kesiapan sumberdaya manusia, tingkat literasi teknologi guru, siswa, dan orang tua serta kesiapan lembaga pendidikan. Tujuan untuk memetakan dan menganalisis bentuk upaya mengatasi kesulitan pembelajaran online era digital selama pandemic Covid-19. Menggunakan metode kualitatif deskriptif, data dikumpulkan melalui data primer dan data sekunder. Data sekunder dari madrasah Tsanawiyah di Bengkulu. Data primer mencakup profiling guru, motivasi, tipe kesulitan dan upaya mengatasi kesulitan yang dialaminya. Data sekunder terdiri dari literasi dan presensi guru, statistic hasil uji kompetensi guru. Data primer dan data sekunder dianalisis sebagai upaya mengatasi kesulitan pengelolaan pembelajaran online era digital selama pandemic Covid-19, dengan mempertimbangkan karakteristik, situasi dan budaya khusus mereka. Studi ini menunjukkan bahwa perbedaan dalam kelompok social ekonomi siswa dan orang tua menyusun peluang mereka untuk belajar online. Kesenjangan kelas social ekonomi siswa memiliki konsekuensi tingkat kesulitan pengelolaan pembelajaran online dalam berkomunikasi, merespon, beraktivitas, berkolaborasi dan mencapai kompetensi serta prestasi siswa. Kesenjangan struktural yang ada menjadi faktor penting dalam menafsirkan realitas kesulitan pengelolaan pembelajaran online di Madrasah Tsanawiyah di Bengkulu. Kata kunci: Kesulitan Pengelolaan Pembelajaran Online, Era Digital, Empirical Study di Madrasah Tsanawiyah Bengkulu